Prevalence and attributable health burdens of vector-borne parasitic infectious diseases of poverty, 1990–2021: findings from the Global Burden of Disease Study 2021 - Yin-Shan Zhu; Zhi-Shan Sun; Jin-Xin Zheng; Shun-Xian Zhang; Jing-Xian Yin; Han-Qing Zhao; Hai-Mo Shen; Gad Baneth; Jun-Hu Chen; Kokouvi Kassegne (Infectious Diseases of Poverty)
Abstract Background Vector-borne parasitic infectious diseases associated with poverty (referred to as vb-pIDP), such as malaria, leishmaniasis, lymphatic filariasis, African trypanosomiasis, Chagas disease, and onchocerciasis, are highly prevalent in many regions around the world. This study aims to characterize the recent burdens of and changes in these vb-pIDP globally and provide a comprehensive and up-to-date analysis of geographical and temporal trends. Methods Data on the prevalence and disability-adjusted life years (DALYs) of the vb-pIDP were retrieved from the Global Burden of Disease, Injuries, and Risk Factors Study (GBD) 2021 for 21 geographical regions and 204 countries worldwide, from 1990–2021. The age-standardized prevalence rate and DALYs rate by age, sex, and sociodemographic index (SDI) were calculated to quantify temporal trends. Correlation analysis was performed to examine the relationship between the age-standardized rate and the SDI. Results Over the past 30 years, the age-standardized prevalence rate and DALYs rate of these vb-pIDP have generally decreased, with some fluctuations. The distribution of vb-pIDP globally is highly distinctive. Except for Chagas disease, the age-standardized prevalence rate and DALYs rate of other vb-pIDP were highest in low-SDI regions by 2021. Malaria had the highest age-standardized prevalence rate (2336.8 per 100,000 population, 95% UI: 2122.9, 2612.2 per 100,000 population) and age-standardized DALYs rate (806.0 per 100,000 population, 95% UI: 318.9, 1570.2 per 100,000 population) among these six vb-pIDP globally. Moreover, significant declines in the age-standardized prevalence rate and DALYs rate have been observed in association with an increase in the SDI . Globally, 0.14% of DALYs related to malaria are attributed to child underweight, and 0.08% of DALYs related to malaria are attributed to child stunting. Conclusions The age-standardized prevalence rate and DALY rates for the vb-pIDP showed pronounced decreasing trends from 1990–2021. However, the vb-pIDP burden remains a substantial challenge for vector-borne infectious disease control globally and requires effective control strategies and healthcare systems. The findings provide scientific evidence for designing targeted health interventions and contribute to improving the prevention and control of infectious diseases. Graphical Abstract